2016
DOI: 10.22146/majkedgiind.11267
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh keadaan rongga mulut, perilaku ibu, dan lingkungan terhadap risiko karies pada anak

Abstract: The effect of oral cavity condition, mothers’ behaviour and environment on the carries risk on children. Carries risk factors in children consist of direct risk factor, which includes the condition of oral cavity, and indirect risk factor including mother’s behaviour and environment. The study was to identify factors that influence the occurrence of caries in children. This is an observational research with a cross-sectional design. The samples were 430 children between the ages of 10-12 years. The evaluated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The results of the study, showed that the increase in the salivary pH of those who brushed their teeth using the toothpaste containing detergent (1.0813) was higher than the increase in the salivary pH of those who brushed their teeth with toothpaste that did not contain detergent (0.7247). 21 Toothpaste that contains detergent is called detergent toothpaste. The detergent used is sodium lauryl sulphate (SLS).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study, showed that the increase in the salivary pH of those who brushed their teeth using the toothpaste containing detergent (1.0813) was higher than the increase in the salivary pH of those who brushed their teeth with toothpaste that did not contain detergent (0.7247). 21 Toothpaste that contains detergent is called detergent toothpaste. The detergent used is sodium lauryl sulphate (SLS).…”
Section: Discussionmentioning
confidence: 99%
“…Faktor-faktor yang berperan secara langsung dalam proses karies adalah plak gigi, mikroorganisme, dan pola makan karbohidrat. 17 Anak umur 8 -10 tahun merupakan satu kelompok yang rentan terhadap penyakit gigi dan mulut karena umumnya anakanak pada umur tersebut masih mempunyai perilaku atau kebiasaan diri yang kurang menunjang terhadap kesehatan gigi. 6 Hal tersebut sejalan dengan penelitian yang dilakukan oleh Vineet Dhar dan Maheep Bhatnagar (2009) dimana anak laki-laki lebih banyak terjadi karies daripada anak perempuan.…”
Section: Pembahasanunclassified
“…21 Pengaruh dari teman sebaya memegang peranan penting dalam sikap anak untuk berkunjung ke dokter gigi, anak akan termotivasi dan meminta orangtuanya untuk mengantar periksa ke dokter gigi, jika mendapat cerita dari teman sebaya bahwa periksa ke dokter gigi itu menyenangkan dan tidak menakutkan. 17…”
Section: Pembahasanunclassified
“…Risk factors are factors that do not have an immediate impact on the development of caries and consist of age, gender, occupation, education, environment, behavior, culture, heredity, and systemic disease. 5,7,8 It has been widely reported that caries increases as people age. This is because the longer the teeth are in the oral cavity, the more frequent the interactions with the factors that cause caries.…”
Section: Introductionmentioning
confidence: 99%